2010
DOI: 10.1056/nejmoa0906626
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapies in Women after Single-Dose Nevirapine Exposure

Abstract: BACKGROUND Peripartum administration of single-dose nevirapine reduces mother-to-child transmission of human immunodeficiency virus type 1 (HIV-1) but selects for nevirapine-resistant virus. METHODS In seven African countries, women infected with HIV-1 whose CD4+ T-cell counts were below 200 per cubic millimeter and who either had or had not taken single-dose nevirapine at least 6 months before enrollment were randomly assigned to receive antiretroviral therapy with tenofovir–emtricitabine plus nevirapine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
91
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 29 publications
0
91
0
1
Order By: Relevance
“…Of the 241 women enrolled in trial 1, 42 women reached a primary endpoint (death or virological failure); about three-quarters of these were in the NVP arm. The distribution of deaths and failures was similar in the two arms: four deaths of 32 endpoints in the NVP arm compared with one death of 9 endpoints in the LPV/r arm (12). Of the 239 women for whom population genotypes were obtained at baseline, 33 had NVP resistance mutations: 15 (13%) of 120 women in the NVP arm and 18 (15%) of 119 women in the LPV/r arm.…”
Section: Trial 1 Primary Study Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Of the 241 women enrolled in trial 1, 42 women reached a primary endpoint (death or virological failure); about three-quarters of these were in the NVP arm. The distribution of deaths and failures was similar in the two arms: four deaths of 32 endpoints in the NVP arm compared with one death of 9 endpoints in the LPV/r arm (12). Of the 239 women for whom population genotypes were obtained at baseline, 33 had NVP resistance mutations: 15 (13%) of 120 women in the NVP arm and 18 (15%) of 119 women in the LPV/r arm.…”
Section: Trial 1 Primary Study Resultsmentioning
confidence: 87%
“…The results of the primary analysis of trial 1 (12), stratified by standard population genotype result at study entry for NVP resistance, are summarized in Fig. 1A.…”
Section: Trial 1 Primary Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHO guidelines, however, provide a second option of zidovudine with single-dose nevirapine (AZT plus sd-NVP), stating that both options have advantages and disadvantages in terms of feasibility, acceptability, safety and cost [103]. The Optimal Combination Therapy After Nevirapine Exposure (OCTANE) study showed inferior outcome after NVP-versus protease inhibitor (PI)-based HAART in women exposed to sd-NVP [1]. A Thai feasibility study showed that the transition to HAART for all HIV-infected pregnant women was acceptable and achievable.…”
mentioning
confidence: 99%